The Effect of Smartphone Addiction and Self-Control on Phubbing Behavior - Isrofin, Binti; Munawaroh, Eem (Jurnal Kajian Bimbingan dan Konseling, 2021)
Phubbing is a behavior of ignoring the interlocutor and focusing more on smartphones. This behavior, which is quite common recently, has a negative impact on social interactions. The purpose of this study was to analyze the effect of smartphone addiction and self-control on phubbing behavior. This study employed a correlational research design. Three hundred and seventy-nine samples involved in this study were recruited using random sampling techniques. The data were collected using the Smartphone Addiction Scale, Phubbing Scale, and Self-Control Scale. The data were analyzed using regression analysis assisted by JASP software version 0.11.10. The findings show that smartphone addiction is a predictor of phubbing behavior by 47 percent, while other factors influence the rest. Self-control was not proven to be a significant predictor of phubbing behavior in the researched participants. An in-depth study of the factors that influence phubbing behavior is encouraged to be investigated for further research.